Detection of pathogens in dogs with respiratory disease during winter 2023–2024 using multiplex qPCR/RT-qPCR assays and next-generation sequencing - Thieulent, Côme J.; Laverack, Melissa; Carossino, Mariano; Cronk, Brittany; Caserta, Leonardo Cardia; Diel, Diego G.; Balasuriya, Udeni B. R. (Frontiers in Veterinary Science, 2025)
Canine Infectious Respiratory Disease Complex (CIRDC), caused by a diverse range of viral and bacterial pathogens, is the leading cause of respiratory illness in dogs. In the winter of 2023–2024, the United States experienced a noticeable increase in cases consistent with CIRDC. This study investigated the potential association of emerging pathogens with CIRDC cases. It involved the analysis of 50 clinical specimens collected from CIRDC-suspected dogs from six US states between December 2023 and February 2024. All clinical cases presented with respiratory illness characterized mainly by coughing (78%), nasal and ocular discharges (30%), and sneezing (22%). Specimens were tested for 12 known CIRDC-associated pathogens using a previously described panel of one-step TaqMan® multiplex qPCR/RT-qPCR assays designed to detect eight viral and four bacterial pathogens. Specimens were also subjected to next-generation sequencing (NGS) to confirm qPCR/RT-qPCR results and identify potential emerging pathogens. In this study, 64% of samples tested positive for various canine respiratory pathogens. Mycoplasma canis was the most frequently detected agent (n = 20), followed by M. cynos (n = 9), canine respiratory coronavirus (n = 3), canine parainfluenza virus (n = 3), and Bordetella bronchiseptica (n = 3). Additionally, canine adenovirus type 2, canine herpesvirus 1, and canine distemper virus were also detected in some samples. NGS also identified canine calicivirus, canine circovirus, and, for the first time, vientovirus in a CIRDC-affected dog. This study indicates that CIRDC cases observed in the winter of 2023–2024 were not associated with the emergence of any new pathogens. The clinical relevance of the detection of vientovirus in a single dog remains unknown.